The role of eNOS in the migration and proliferation of bone‐marrow derived endothelial progenitor cells and in vitro angiogenesis. (5th January 2015) - Lu, Aizhen; Wang, Libo; Qian, Liling
Abstract: The role of endothelial nitric oxide synthase (eNOS) in the activities of endothelial progenitor cells (EPCs) including migration, proliferation, and tube formation in vitro was investigated. EPCs were obtained from rat bone mononuclear cells by culturing for 7–10 days in EGM‐2MV and identified by their capacity for FITC‐UEA‐1 binding and acetylated low‐density lipoprotein (Dil‐ac‐LDL) intake using fluorescence microscopy. Migration, proliferation and tube formation activities were assessed in the presence or absence of N ω ‐nitro‐L‐argininemethylester (L‐NAME), an eNOS inhibitor. mRNA and protein expression of CXCR4, CXCR7, VEGFR2, and eNOS were detected by real‐time PCR and western blotting in the presence or absence of L‐NAME. Nitric oxide production was detected by nitrate reductase in the presence or absence of L‐NAME. Typical spindle‐shaped cells appeared on the 7 th –10 th day and confluence reached about 80%. The percentage of FITC‐UEA‐1 and Dil‐ac‐LDL double‐stained cells was about 85%. Cell migration, proliferation, and tube formation were significantly weakened after eNOS was inhibited ( P < 0.05), and the expressions of CXCR4 and eNOS were significantly reduced ( P < 0.05, respectively), but there was little change in CXCR7 and VEGFR2. NO production was dramatically decreased after eNOS was inhibited ( P < 0.05). In summary, L‐NAME significantly reduced the expression of eNOS and NO production by EPCs and inhibited migration, proliferation and tube formation by these cells, suggesting that eNOS affects EPC activities; CXCR4 may be implicated in the action of eNOS.